Penerapan Strategi Pembelajaran Interaktif dalam Mengatasi Kesulitan Membaca pada Siswa Sekolah Dasar - Mursida; Az-Zahra, Fatimah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Reading ability is a fundamental foundation in the learning process at the primary education level. However, many early grade students still face difficulties in reading, either due to monotonous teaching methods or a lack of active student involvement in the learning process. This research aims to find out how the strategies implemented by teachers enhance reading skills among first-grade students and to identify the inhibiting factors that affect the development of these skills. The method used in this research is a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The subjects of the research are first-grade teachers, students, and the principal. The research results indicate that the use of flashcard-based learning strategies significantly enhances students' reading abilities. Students become more enthusiastic, active, and show progress in recognizing letters and reading short sentences. However, there are still challenges such as a less conducive learning environment, minimal parental involvement at home, and low student motivation. The implications of this study emphasize the importance of implementing interactive, creative learning strategies that align with students' characteristics to optimize reading skills in early elementary school.